METHODS OF DISTINGUISHING PHYTONEMATODES IN PLANTS - E. Q. Abduraxmonova (Web of Journals Publishing, 2024)
Information is given on the methods used in the isolation and study of plant nematodes. The advantages, disadvantages and features of the methods are mentioned.
Keywords: Mashrut, compressor, funnel methods and their application.